Implementasi Pembangunan Gapura Dan Tanaman Obat Keluarga (TOGA) Dalam Pembangunan Prasarana Di Desa Sei Sijenggi - Abdi Rianto; Dahlia Dahlia; Vebiola Ardiani; Alkausar Saragih (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this research is to build a gate and plant family medicine. The assistance and support provided by village officials and villagers. Researchers created a program to build a gate in Sei Sijenggi Perbaungan village, precisely in Hamlet IV so that tourists can easily find Hamlet IV. Then in addition to building the Gapura, researchers also made Toga plants called family medicinal plants in Hamlet IV as well. With the villagers who helped in finding land for planting Toga, it made it easier for researchers to plant the Toga, the function of planting Toga, so that Sei Sijenggi villagers use traditional medicines for consumption when they are sick. The approach used in this research is qualitative. In this study, researchers collaborated with residents to carry out this research program. Building Gapura and maintaining and preserving family medicinal plants that researchers have made must have community participation and mutual cooperation